Severe and Refractory Hypertension in a Young Woman - Cuadra, René H (J Am Soc Hypertens, 2016)
BACKGROUND: Refractory hypertension in a young person is an uncommon clinical problem, but one that may be referred to hypertension specialists. Factitious hypertension is fortunately quite rare, but should be considered when evaluating patients who are refractory to numerous classes of antihypertensive therapies and have failed to achieve control despite input from multiple providers. REPORT OF A CASE: A 19 year old woman was referred to us after failing to achieve blood pressure control by a primary physician and 2 subspecialists in nephrology and hypertension; she also had numerous emergency department visits for symptomatic and severe hypertension. Exhaustive diagnostic testing for secondary causes and witnessed medication dosing in an outpatient setting was unrevealing. Subsequent inpatient admission demonstrated normalization of BPs with small doses of intravenous antihypertensive agents. During the hospitalization, she was observed “pocketing” her oral medications in the buccal folds, and then discarding them in a trash container. Confrontation by psychiatrists and the hypertension specialists led to the admission that she had learned to start and stop beta-blockers and clonidine to induce severe, rebound hypertension. DISCUSSION: Factitious and induced hypertension is a rare cause of resistant or refractory hypertension. Nevertheless, hypertension specialists should suspect the diagnosis when there is a history of visits to multiple institutions and physicians, negative secondary workup, absence of overt target organ damage, history of psychiatric illness, and employment in the medical field.